PENGARUH TV STREAMING TERHADAP PERTUMBUHAN INDUSTRI EKONOMI KREATIF DAMPAKNYA TERHADAP PENYERAPAN TENAGA KERJA - Rinny Yudowati; Linda Fitriyanti (Journal of Information System, Applied, Management, Accounting and Research, 2020)
This study aims to determine the effect of TV Streaming on the growth of the Creative Economy Industry and its impact on Labor Absorption. Seeing the rapid digital development and the shifting of people's behavior from print media, television and radio to digital media, one of which is Streaming TV. It is predicted that in the future live streaming industry will become a trend and increasingly used in Indonesia. By using the Slovins theory, 100 samples of the perpetrators and users of TV streaming in Jakarta were obtained. Two approaches were carried out, namely the descriptive approach by describing the existing phenomena and quantitative in which data collection used observation and interview techniques. The research location was conducted in the Jakarta area. The independent variable is TV Streaming, the intervening variable is Creative Industry Growth and the dependent variable is labor absorption. The data source in this study is the internet user community obtained from the Indonesian Internet Service User Association (APJII) in 2018 and BPS. The results showed that Media TV Streaming had an effect on the growth of the Creative Economy Industry and had an impact on Labor Absorption.